IMPLEMENTATION OF LEAN HOSPITAL AS AN EFFORT TO IMPROVE HEALTH SERVICES IN THE EMERGENCY UNIT OF THE HOSPITAL - I Gusti Nyoman Trianantha Jaya; Kosasih; Farida Yuliaty; Vip Paramarta; Fitriana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Service emergency emergency at home Sick often face​ challenge like overcrowded and false emergencies, which resulted in a decline quality service and improvement time Wait patient. Research This aiming For analyze implementation Lean Hospital as effort improvement efficiency and quality services in the Emergency Unit Emergency (ER). Lean hospital adopt principles subtraction waste includes​​​ time excessive waiting, usage​ source suboptimal power, and administrative processes that are not own mark add. Method study This use source from journal scientific, articles, books scientific, as well as guidelines House sick. Study results show that implementation lean hospital capable reduce time Wait up to 30%, increasing flow work, and optimize utilization source power that has an impact on increasing satisfaction patients and decline risk error medical. In conclusion, Lean Hospital is a approach effective management​ in increase efficiency and quality service health in the ER, as well as capable face challenge operational House the pain is getting worse complex in this modern era.